The Influence of Product Variation, Price, and Marketing Communication Strategy on Purchase Decisions for Used Clothing at Medan's Melati Market - Agita Trianto; Mesra B; Annisa Sanny (Universitas Dehasen Bengkulu, 2026)
This study aimed to analyze the effect of product variety, price, and marketing communication strategy on purchasing decisions for secondhand clothing at Pasar Melati Medan. The study employed a quantitative approach with an associative method. The population of this study consisted of all customers of secondhand clothing at Pasar Melati Medan, whose exact number was unknown, with a sample of 96 respondents determined using the Zikmund formula and accidental sampling technique. Primary data were obtained through questionnaire distribution and processed using SPSS version 24 software. Data analysis was conducted using multiple linear regression to examine the relationships between independent and dependent variables. The results showed that product variety, price, and marketing communication strategy, both partially and simultaneously, had a positive and significant effect on purchasing decisions for secondhand clothing at Pasar Melati Medan. Price became the most dominant variable influencing purchasing decisions, as indicated by the highest regression coefficient value. All hypotheses H1, H2, H3, and H4 were proven and accepted, as the research findings were consistent with the proposed hypotheses. The resulting regression equation was Y = 3.339 + 0.273X1 + 0.440X2 + 0.242X3 + e, with all independent variables having t-count values greater than t-table values and significance levels below 0.05. The coefficient of determination (adjusted R²) of 0.866 indicated that 86.6% of the variation in purchasing decisions was explained by the three independent variables, while the remaining 13.4% was explained by other variables not included in this research model. In addition, the strength of the relationship between the independent variables and the dependent variable was classified as very strong, with a correlation coefficient (R) value of 0.933.